How dangerous is human resource management? a reply to Tim Hart - Torrington, Derek (1993)
A reaction to an article in a previous issue of the journal about the dangers of Human Resource Management (HRM). HRM was described as amoral, anti-social, uneconomic and ecologically destructive. Whilst accepting that HRM is flawed, argues that its acceptance is partly attributable to the dependence of management researchers on the approval of research councils and employers. Concludes with suggestions for personnel managers to consider: less obsession with strategy at the expense of operations; less preoccupation with management at the expense of other members of the business; and much greater preoccupation with the recreation of employment.